Advanced online fuel cell stack water management strategies for fuel cell stacks in vehicle powertrain control - Duan, Yu; Li, Yu; To, Daniel; Zhang, Jiaxiang; Chen, Jinrui; Ran, Hongxu; Fan, Min (Frontiers in Energy Research, 2025)
Effective water management is crucial for the optimal performance and durability of proton exchange membrane fuel cells (PEMFCs) in automotive applications. Conventional techniques like electrochemical impedance spectroscopy (EIS) face challenges in accurately measuring high-frequency resistance (HFR) impedance during dynamic vehicle operations. This study proposes a novel stack water management stability control and vehicle energy control method to address these limitations. Simulation and experimental results demonstrate improved system and powertrain efficiency, extended stack lifespan, and optimized hydrogen consumption. These findings contribute to advancing robust water management strategies, supporting the transition toward sustainable, zero-emission fuel cell vehicles.